Food Biodiversity as an Opportunity to Address the Challenge of Improving Human Diets and Food Security - Jacob, Michelle; Medeiros Souza, Alice; Martins de Carvalho, Aline; Alves de Vasconcelos Neto, Carlos Frederico; Tregidgo, Daniel; Hunter, Danny; de Oliveira Pereira, Fillipe; Ros Brull, Guilhermo; V. Kunhlein, Harriet; Guedes da Silva, Lara Juliane; Mont'Alverne Jucá Seabr, Larissa; Drewinski, Mariana de Paula; et al. (Ethnobiology and Conservation, 2023)
Scientists have warned for several years that food systems have become major drivers of environmental degradation, malnutrition, and food insecurity. In this paper, we present arguments from specialists that suggest that, in the transition to more sustainable food systems, biodiversity and food security can be mutually supportive, rather than conflicting goals. We have divided the opinions of these scientists into two "Big Topics". First, they examine the synergies and challenges of the intersection of biodiversity and food security. In the second section, they explain how various forms of food biodiversity, such as mushrooms, terrestrial wild animals, aquatic animals, algae, and wild plants, can contribute to food security. Finally, we present three main pathways that, according to these experts, could guide the transition toward biodiversity and food security in food systems.